The pre-sizing approach of dc-dc converters as the application to design a buck converter for the automotive domain - Noor Suhada, Ab Razak (2010)
Choosing the right DC-DC converter for automotive applications can be a challenging task when one considers all the requirements that need to be met. The requirement for vehicles increased continuously in the 20th century as consumers required more from their vehicles. Because of that, car manufacturers have provided both standard and optional equipment to meet these demands. In this project, a prototype of DC-DC Converter is designed and developed. This converter includes buck converter, controller, and driver. The purpose of this project is to propose a presizing approach that includes a step to formalize the converter architecture and component choices and to design a Buck converter system in order to produce the desired voltage that suitable for automotive domain. This approach can be conducted in two steps. The first step is by the calculation to find the specific parameter for the design. The second step uses specific models developed from the manufacturer datasheets as reference to choose the architecture and appropriate component technologies and will be applied to pre-size a Buck DC-DC power converter for the automotive domain. The pre-sizing results will show the specifications that respected to the proposed approach.